To Assess The Knowledge of Mothers on Hunger Cues in Infants Less Than 6months Under Different Feeding Methods - Shanmuganathan. R, Shanmuganathan. R; MD, Deepan; MD, Alexander mannu.; Rajkumar MD, G. (Journal of Neonatal Surgery, 2025)
Background Mothers’ perception of infant hunger cues is a critical content of responsive feeding, which is central to the promotion of early childhood development. However, only a few studies have examined responsive feeding in India, especially lacking the studies on perceptions of infant hunger cues.the aim of this study was to describe the perceptions of infant hunger cues of mothers for infants aged 6 months, and explore the relationship between maternal perceptions of infant hunger cues and different feeding methods. Methods A cross-sectional study was conducted with a sample of 200 mothers of healthy infants. The study involves mothers filling out a previously tested structured questionnaire, which is provided after getting consent in both English and Tamil. The questionnaire has been pre-validated by our expert team. This study does not involve any other interventions. The aim of this study is to observe the responses from the questionnaire and come to conclusions about mothers' understanding of hunger cues in infants under six months under various nutritional methods. Mothers are recruited from postnatal wards, regular OPD visits , and vaccination OPD visits. The inclusion criteria are as follows: (a) the child must be full-term (≥ 37 weeks); (b) the child's birth weight must be 2000 grams or more; (c) the child must have been exclusively breastfed in the past 24 hours and no other foods (except medications and vitamins) added (for children in the EBF group), or not exclusively breastfed in the past 24 hours (for children in the FF group). The above information was obtained through interviews, and mothers were given sufficient time to reflect on their responses. Exclusions include: (a) children with health problems that could affect feeding abilities (for example, swallowing); (b) mothers or children with severe health problems that could affect the child's growth and/or development and/or include the mother's prenatal and/or postnatal complications; (c) mothers without reading and writing skills. Results: sis revealed that EBF might support mothers to perceive infant hunger cues than FF mothers, with the number of infant hunger cues (OR = 1.70, 95% CI: 1.01–2.85), “hand sucking” (OR = 1.72, 95% CI: 1.04–2.87), “moving head frantically from side to side” (OR = 2.07, 95% CI: 1.19–3.62). The number of infant hunger cues perceived by mothers was also associated with their educational level and family structure. Conclusion: EBF mothers of 6-month-old infants may be more likely to perceive infant hunger cues than FF mothers. It is necessary to increase the health education about infant hunger and satiety cues to caregivers, especially among mothers with lower education levels, mothers living in nuclear families, and FF mothers.